A Mild and Efficient Procedure for the N-Functionalization of S-Perfluoroalkylated Aryl Sulfoximines - Macé, Yohan; Constant-Urban, Céline; Bouvet, Sébastien; Pégot, Bruce; Bournaud, Chloée; Toffano, Martial; Vo-Thanh, Giang; Diter, Patrick; Magnier, Emmanuel (Synthesis, 2013)
N-Acylated perfluoroalkylated sulfoximines are synthesized easily from the corresponding free NH-sulfoximines on reaction with acid chlorides. This mild procedure is extended to diacid chlorides for the preparation of dimeric N-bridged sulfoximines and to reactions with chloroformates, carbamoyl chlorides, chlorothionoformates and thiocarbamoyl chlorides as electrophiles.
Keywords: fluorinated sulfoximines; acylation; carbamoylation; ureas; N-bridged sulfoximines